The Web Beneath the Waves: The Fragile Cables That Connect Our World. - EICHENGREEN, BARRY (Foreign Affairs)
The article focuses on the significance of subsea fiber-optic cables in global communication and their role in modern economies. These cables, which connect over 100 coastal states and facilitate more than 98 percent of intercontinental Internet and telecom traffic, are essential for globalization and international transactions. The author discusses the shift from a telecommunications consortium model to one led by technology companies like Google and Meta, highlighting the vulnerabilities of this infrastructure to espionage and sabotage by various governments, including the United States, China, and Russia. The text underscores the critical nature of these cables and the geopolitical tensions surrounding them.